(untitled) (Medico Legal Update, 2021)
Communicable diseases are an illness that is transmitted from a person, animal, or inanimate source to another person either directly, with the assistance of a vector or by other means. Communicable diseases are a major cause of mortality and morbidity in emergencies, and particularly in complex emergencies, where collapsing health services and disease control programs. They are the basic level of infectious pathogens control precautions which are to be used, as a minimum, in the care of all patients. A quasi-experimental design (descriptive study) used to guide this study; it was applied by use of pretest-posttest approach for two groups of samples (study and control) Non- probability (purposive) sample of (80) nurses who are working in Al-Nasiriyah city hospitals. The findings of the current study revealed that there are highly statistically significant differences in posttest. The study concludes that there is poor and low level of knowledge assessment among the participants toward communicable diseases control at the pre-test in the both group. The results show after the implementation of educational program high level of nurses’ knowledge for (post-test I and post-test II) for the study group regarding communicable diseases control. The study concludes there were no significant association between nurses’ knowledge and their socio demographic characteristics includes: age; gender; level of education and years of experience. The study recommends of the providing an educational and training program periodically for nurses in order to enhancement the level of their knowledge regarding communicable diseases control.